Amazonimyia gigantea gen. n., sp. n., a new Tanypodinae (Diptera: Chironomidae) from the Neotropical Region - Da Silva, Fabio Laurindo; Wiedenbrug, Sofia (Zootaxa, 2015)
A new genus, Amazonimyia, is established for a species of the tribe Pentaneurini (Diptera, Chironomidae, Tanypodinae) from the Amazon Rainforest in northern Brazil. Generic diagnoses for adult male and pupa are provided together with descriptions of a new species, Amazonimyia gigantea.